A career development perspective among young adults cancer survivors - Musa, Siti Nur Syuhada; Hamzah, Siti Raba'ah; Asmiran, Soaib; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2020)
The purpose of this paper is to study on the understanding of the concept of career development among cancer survivors who were diagnosed with cancer during their childhood. This study was based on review of past researches on individual factors and career development among cancer survivors using the System Theory Framework. To conduct the literature reviews, the researcher utilized keywords such as career, career development and cancer survivors. From the literatures reviewed, the single factor that contributed to career development among young cancer survivors was the individual factor. Hence, addressing career development (the individual factor), might be important to improve employment outcomes for young cancer survivors. The importance and originality of this study were, it explored career development among young cancer survivors. This paper adopted elements from the System Theory Framework (STF) to derive the individual factor that influenced of career development. It is hoped this research findings will contribute to literatures on the significant factor contributing to career development among young cancer survivors in Malaysia.